Integrating TAM, VAM, PAM And Security Perception In The Intention Of Fintech Service Usage - Aglis Andhita Hatmawan (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This study is aims to develop a TAM (Technology Acceptance Model) by integrating a VAM (Value-based Adoption Model), PAM (Pos Acceptance Model) and security perceptions. The frameworks of the theories are expected to deeper explain the perspective perceived by fintech services users in terms of security, perceived value, benefits and satisfaction in using fintech. Survey through a quantitative approach combined with explanatory research in Madiun Residency are used in this research. The results showed that all hypotheses proposed in this study were accepted. Security is the main requirement for people to continue or discontinue using fintech services. Perceived value is a comparative result influenced by the amount of sacrifice made and the perceived benefits. People who are satisfied and tends to assume that the fintech service is valuable, will have a tendency to continue using the fintech service. Therefore, it can be concluded that TAM, VAM, PAM and security perceptions are a unified whole in understanding one's behaviour in adopting technology such as fintech servicces.